DESKRIPSI KEMAMPUAN REPRESENTASI MATEMATIS PESERTA DIDIK KELAS XI DALAM MENYELESAIKAN MASALAH MATRIKS - Siti Komariah; Ressy Rustanuarsi; Yumi Sarassanti (Uninus Journal of Mathematics Education and Science (UJMES), 2025)
This study aims to describe the mathematical representation abilities of eleventh-grade students in solving matrix problems. A qualitative approach with a case study design was employed. The research participants consisted of six students selected from a total of 29 students in Class XI MIPA 4 at SMAS Mujahidin Pontianak. Participants were chosen through purposive sampling based on three levels of mathematical ability (high, moderate, and low) with two students representing each category. The study analyzed students' representation abilities across three dimensions, namely visual, symbolic, and verbal. Data were collected through written tests and interviews. The data analysis process involved three stages: data condensation, data display, and conclusion drawing. The results revealed that students with high ability demonstrated comprehensive mastery of all three forms of representation. Students with moderate ability showed sufficient proficiency in visual and symbolic representation but had limitations in verbal representation. Meanwhile, students with low ability encountered difficulties in all three aspects. These findings suggest that teachers should design instructional strategies and tasks that promote students' abilities to make conjectures, interpret, justify, and connect mathematical ideas, thereby enhancing students' mathematical representation abilities.